(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
Maize (Zea mays L.) yield in Angola is severely affect by Spodoptera frugiperda which is often controlled with conventional insecticides in spite of various ecological problems. An effective alternative could be the use of aqueous plant extracts with clear insecticide properties such as the Ricinus Communis L. Therefore, the present study investigated the effect of Ricinus communis L. leaf extract at different concentration on the mortality of Spodoptera frugiperda fed with maize leaves soaked in the Ricinus communis L. extract. The extract was obtained from 10g of fine grinded Ricinus communis L. leaves and diluted with distilled water. Different concentrations were evaluated and its efectividade in the control of the plague. The results showed that aqueous Ricinus communis L. extract was effective in killing Spodoptera frugiperda, with an increasing mortality over time where the highest mortality was observed at 75% and 100% extract concentration. Nonetheless, mortality of Spodoptera frugiperda was further increased after 72 h when an extract at 75 or 100% concentration was used.